World's landlocked basins drying. Issue 12 (December 2018) - Pavelsky, Tamlin
Most of the net water transferred over the past 15 years from non-glaciated land to the oceans has originated from landlocked basins, according to satellite data. This source of sea-level rise is often overlooked.